If it's not what You are looking for type in the equation solver your own equation and let us solve it.
5(w-1)-w=3(w-1)+7
We move all terms to the left:
5(w-1)-w-(3(w-1)+7)=0
We add all the numbers together, and all the variables
-1w+5(w-1)-(3(w-1)+7)=0
We multiply parentheses
-1w+5w-(3(w-1)+7)-5=0
We calculate terms in parentheses: -(3(w-1)+7), so:We add all the numbers together, and all the variables
3(w-1)+7
We multiply parentheses
3w-3+7
We add all the numbers together, and all the variables
3w+4
Back to the equation:
-(3w+4)
4w-(3w+4)-5=0
We get rid of parentheses
4w-3w-4-5=0
We add all the numbers together, and all the variables
w-9=0
We move all terms containing w to the left, all other terms to the right
w=9
| 6-2(x=3)=1=4x | | 5y-4=2y-2 | | 2(x+3)(x+2+3)-3=3 | | 4a+4=4+5a | | 7(h+7)+3=94 | | 7n+5=5n+50 | | x*(x+2)=3 | | 7(w+-23)=-70 | | 9x=12=x+11 | | 5n-10=3n+27 | | 99×x/9=33 | | 5k+5=85 | | (y-6)/2=1 | | 2(q+-22)+-33=19 | | (d-64)/7=3 | | (d+5)/3=4 | | -2(t+-1)=0 | | 12.2-2x=3.8 | | (3x+1)÷4=(5x-2)÷5 | | (n+9)/3=-1 | | 3p-2.9=7 | | X=25+3y | | 3(h+1)+3=9 | | 4(c+7)=-12 | | 2-x/4=x/5 | | x10=107 | | x÷6=13÷7 | | x5=−5 | | 2x*x=10^2 | | 8^4n=2^48 | | 4x+-3=7+9x | | 2x-8*4=5 |